Epidemiology and etiology of diarrhea in UK military personnel serving on the United Nations Mission in South Sudan in 2017: A prospective cohort study. Issue 28 (March 2019) - Biswas, Jason S.; Lentaigne, Julian; Hill, Neil E.; Harrison, James J.; Mackenzie, Hector; Akorli, Ernest; Burns, Daniel S.; Hutley, Emma J.; Connor, Patrick; Woods, David R.
Abstract: Background: . Diarrhea is a well-established problem in travellers, with military personnel at especially high risk. This study aimed to characterise the spectrum of pathogens causing diarrhea in UK military personnel in South Sudan, and assess the utility of culture-independent testing for etiology and antimicrobial resistance in a logistically challenging and austere environment. Methods: . All military personnel presenting with diarrhea were admitted to the UK Level 2 Medical Treatment Facility in Bentiu, South Sudan. Samples were tested for etiology utilising multiplex PCR-based diagnostics (BioFire FilmArray). In addition, the presence of carbapenemase resistance genes was determined using the geneXpert Carba-R platform. Results: . Over 5 months, 127 samples were tested. The vast majority of pathogens detected were diarrheagenic Escherichia coli . The presence of either enterotoxigenic (ETEC) or enteropathogenic (EPEC) E. coli was a significant predictor of the other being present. In this study patients presenting with vomiting were 32 times more likely to have norovirus than not (p < 0.001). No carbapenem resistance was detected. Conclusions: . Diarrhea in UK military personnel in South Sudan was determined to be predominantly bacterial, with norovirus presenting a distinct clinical and epidemiological pattern. Multiplex PCR and molecular resistance point of care testing were robust and effective in this environment.